Integrating Guided Inquiry with Islamic Values: Managing Islamic Education to Foster Character and Critical Thinking - Sholihah, Lilis; Hasanah, Aan; Hariman, Hariman; Nurhamzah, Nurhamzah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to develop and validate the Islamic Value-Based Guided Inquiry (GI-BNI) model to improve students’ conceptual mastery and character development in Islamic Religious Education. The research method uses Research and Development (R&D) with the Thiagarajan model through the 4D approach (Define, Design, Develop, Disseminate). This study combines quantitative and qualitative methods (mixed methods), including tests, questionnaires, observations, and interviews, and uses the mean difference test for quantitative analysis. The results show that the developed model comprises eight phases (Open, Immerse, Explore, Identify, Gather, Create, Share, Evaluate) integrated with Islamic values (faith, honesty, responsibility, and tolerance). Expert validation shows 93.33% feasibility, and implementation in Praja Pratama classes achieves an average observation score of 87.4%. This model is effective, as evidenced by increases in Islamic Religious Education (PAI) learning scores (meeting I: 58.24 to 73.23; meeting II: 66.17 to 84.5; meeting III: 55.34 to 81.78). This model also has a significant impact on student behavior (93.48%). Supporting factors include the learning environment, lecturers, students, and curriculum. This study concludes that the eight-phase model and Islamic values are effective in Islamic Religious Education (PAI) learning and changing student behavior.